Coastal Sediments 2019 2019
DOI: 10.1142/9789811204487_0146
|View full text |Cite
|
Sign up to set email alerts
|

Scale Experiments on Aeolian Deposition and Erosion Patterns Created by Buildings on the Beach

Abstract: Worldwide, buildings are present at the beach and in the dunes for recreation or habitation. Their presence can affect the beach-dune development, because they affect the airflow and Aeolian sediment transport in their surroundings. This might eventually have repercussions for coastal safety. We start examining these effects by studying the local sedimentation and erosion patterns around buildings. Hereto, we placed scale models of buildings on the beach. The sedimentation and erosion patterns around the model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Furthermore, a higher building impacts the wind velocity magnitudes for a longer distance downstream the building. The horizontal divergence of the velocity field is then calculated for one case, shown in Figure 7a, and the results are compared with the field measurements of erosion and sedimentation patterns around scaled buildings at the beach, shown in Figure 7b, done by Poppema et al (2019). The divergence of the velocity field represents the rate of flow inward or outward from a given point, therefore the results of the horizontal divergence of the velocity field can be helpful for predicting the aeolian erosion and deposition patterns around a building.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a higher building impacts the wind velocity magnitudes for a longer distance downstream the building. The horizontal divergence of the velocity field is then calculated for one case, shown in Figure 7a, and the results are compared with the field measurements of erosion and sedimentation patterns around scaled buildings at the beach, shown in Figure 7b, done by Poppema et al (2019). The divergence of the velocity field represents the rate of flow inward or outward from a given point, therefore the results of the horizontal divergence of the velocity field can be helpful for predicting the aeolian erosion and deposition patterns around a building.…”
Section: Resultsmentioning
confidence: 99%
“…Results of the a) numerical predictions of the horizontal divergence of the velocity field, and b) field measurements of erosion and deposition patterns around a scaled building(Poppema et al, 2019).…”
mentioning
confidence: 99%
“…For instance, Boers et al (2009) used a wave basin to study storm erosion of a scaled dike-and-dune system; wind flow around buildings or over dunes can be studied in wind tunnels (e.g. Fackrell, 1984;Wiggs et al, 1996 (Poppema et al, 2019).…”
Section: Physical Models -Scaled Lab Experimentsmentioning
confidence: 99%
“…The morpholog-ic change is derived from the conservation of sediment. Simulations can be made for full scale beach houses, but also at the scale of the physical model experiments at the beach by Poppema et al (2019) to support interpretation of observed sedimentation patterns in terms of underlying mechanisms and test for possible scaling effects.…”
Section: Physical Models -Scaled Lab Experimentsmentioning
confidence: 99%
“…Diversion of wind around beach buildings causes wind to accelerate (picking up sediment) and decelerate, leading to local deposition of sediment on the lee sides, or the formation of 'Sand tails'. The deposition starts in horse-shoe patterns (Poppema, 2019), but can accumulate in combined tails at the back of the building under changing wind conditions as illustrated by GIS-analysis (Van Bergen, 2020) and fieldwork (figure 8). The surplus in deposition can be used for the local harvesting of sediment (e.g.…”
Section: A: Mobilization Of Windmentioning
confidence: 99%